2010
DOI: 10.5539/jsd.v3n3p212
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Willingness to Pay for Entrance Permit: The Evidence from Taman Negara National Park

Abstract: Non-market techniques such as Travel Cost Method (TCM) and Contingent Valuation Method (CVM) are commonly used to estimate the economic benefits of outdoor recreation. This study applied the CVM, with Willingness to Pay (WTP) as the elicitation method, to investigate the pattern of willingness to pay among visitors of Taman Negara National Park (TNNP). In applying CVM, the respondents were asked on the maximum amount they were willing to pay to enter this park. Data were obtained using closed-ended questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 10 publications
1
18
1
1
Order By: Relevance
“…Other studies have found that nationality and degree of attachment to locations affect preferences (e.g., Brouwer et al, 2010;Carlsson et al, 2012;Dallimer et al, 2014;Davis and Tisdell, 1998;Hanley et al, 2003;Ressurreição et al, 2012;Samdin et al, 2010;Yau et al, 2014;Valasiuk et al, 2017). Conversly Dumalisile et al (2005), Horton et al (2003), and Jin et al…”
Section: Possible Reasons and Consequencesmentioning
confidence: 98%
“…Other studies have found that nationality and degree of attachment to locations affect preferences (e.g., Brouwer et al, 2010;Carlsson et al, 2012;Dallimer et al, 2014;Davis and Tisdell, 1998;Hanley et al, 2003;Ressurreição et al, 2012;Samdin et al, 2010;Yau et al, 2014;Valasiuk et al, 2017). Conversly Dumalisile et al (2005), Horton et al (2003), and Jin et al…”
Section: Possible Reasons and Consequencesmentioning
confidence: 98%
“…The perceived benefits of information gained by long-term monitoring must justify its costs (Caughlan and Oakley 2001). In previous studies, researchers have estimated WTP for experiencing high-quality natural environments (Samdin et al 2010, Sekar et al 2014) and viewing charismatic animals (Loomis et al 2000, Rogers 2013), but we know of only one other previous study that has estimated WTP for the scientific monitoring of natural areas and their ecosystem components (Swallow and Liu 2017). We found that the average respondent had a positive WTP for longterm monitoring programs.…”
Section: Discussionmentioning
confidence: 82%
“…In previous studies, researchers have estimated WTP for experiencing high‐quality natural environments (Samdin et al. , Sekar et al. ) and viewing charismatic animals (Loomis et al.…”
Section: Discussionmentioning
confidence: 99%
“…But very few researches have been employed in Malaysia to evaluate the economic value of the cultural goods for the social benefits across the whole nation. Most of the local researches were focused on environmental and ecological economics studies and yet no researches have been initiated on evaluation of the cultural sites for their heritage conservation (Bann, 1999;Mulok, 2008;Radam & Mansor, 2005;Samdin, 2010). The individual preferences, as measured by their WTP value for the cultural heritage conservation, should be given due consideration in decision-making process in order to promote sustainability of a heritage site.…”
Section: Introductionmentioning
confidence: 99%